Tectura taurinensis Gray 1847 ... - Kiel, Steffen; Sami, Marco; Taviani, Marco (Zenodo, 2023)
Tectura ? cf. taurinensis Sacco, 1897 Fig. 5M–N Tectura taurinensis Sacco, 1897: 20, pl. 2 fig. 53. Tectura cf. taurinensis – Cossmann & Peyrot 1917: 34, pl. 2 figs 47–49. Tectura taurinensis – Ferrero Mortara et al. 1984: 279, pl. 51 fig. 3. Material examined ITALY – Tuscany • 1 spec.; Ca’ Cavalmagra; MSF 1310 (L = 2.4 mm). Remarks Sacco (1897) reported this species from the Turin hills and as being 4–6 mm long and up to 1.5 mm high. This matches the size of the specimen from Ca’ Cavalmagra. However, as protoconch and shell microstructure of this species remain unknown, its assignment to the patellogastropod Tectura remains tentative. Stratigraphic and geographic range Middle to Upper Miocene, northern Italy. ... : Published as part of Kiel, Steffen, Sami, Marco & Taviani, Marco, 2023, Mollusks (Gastropoda, Bivalvia) from Miocene cold-seep deposits in northern Italy: revisions and additions, pp. 115-160 in European Journal of Taxonomy 910 on page 127, DOI: 10.5852/ejt.2023.910.2365, http://zenodo.org/record/10350702 ...